Studi Perbandingan Karakteristik Data Klimatologi Stasiun Badan Meteorologi Klimatologi dan Geofisika (BMKG) Aceh - Lores Sudarta; Ichsan Syahputra; Muhammad Zardi; Cut Rahmawati (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
Data used in this case study, rainfall data (mm), temperature (ᵒC), humidity (%), duration of sun exposure (hours), wind speed (m / s). Data collection methods used in this study include, primary data obtained directly by conducting field research using Davis Vantage VVE 6250 Wireless Weather Station. And secondary data is obtained online from the official website data onlineBMKG.go.id. by taking data from 2010 to 2019 in a period of 10 years. With research locations: Mandiri Station, Lambaro Skep, Kuta Alam, Banda Aceh City. Class I Meteorological Station, Sultan Iskandar Muda, Aceh Besar. Meteorological Station Class IV, Lampanah Teungoh, Indrapuri, Aceh Besar. Cot Ba'u Class III Meteorological Station, Sukajaya, Sabang City, Aceh. Malikul Saleh Meteorological Station, Lhoksmawe, North Aceh. Cut Nyak Dhien Meteorological Station, Nagan Raya. Frequency analysis parameters include the parameter average value, standard deviation (Sd), coefficient of variation (Cv). Kurtosis Coefficient (CK) Calculation of these parameters is based on the record of the average daily rainfall of the maximum maximum of the last 10 years. Analysis of rainfall frequency distribution and birthday period (PUT). Analysis of Normal Distribution, Normal Log Distribution, Pearson Type III Log Distribution, Gumbel Distribution, and for analysis methods using isohyet methods, and arithmetic.